Speaking Test Anxiety of The Students In The English Study Program of IAIN Palangka Raya - Wira Rizki Pratama; Sabarun; Zaitun Qamariah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
Anxiety is a person's feeling of fear of something that will be faced and can appear suddenly without being realized by students in certain situations. Anxiety that occurs in students, especially students in English study programs, usually occurs because of several things, such as fear of not speaking English well and fear of not being able to answer the English test. This study tries to explore students' anxiety in oral tests at the English Study Program of IAIN Palangka Raya. The purpose of this study is to explain what are the main causes of student anxiety in the oral test at the IAIN Palangka Raya English Study Program and explain what the solutions are to prevent student anxiety in the oral test at the IAIN English Study Program. Palangka Raya. This study uses a qualitative descriptive method and is equipped with a questionnaire. This study found several main causes of student anxiety in oral tests, such as lack of confidence and fear of being unable to answer the lecturer's questions. Some solutions to prevent anxiety on oral tests include practising in front of a mirror and with classmates.